Differential Scanning Calorimetry, NBO and Hyperpolarizability Analysis of Yohimbine Hydrochloride - Joshi, Bhawani Datt; Tandon, Poonam; Jain, Sudha (Himalayan Physics, 2012)
Yohimbine (C21H27N2O3) is one of the most important indole alkaloid. Differential scanning calorimetry, natural bond orbital (NBO) analysis and dipole moment with hyperpolarizability have been performed for molecular characterization. Stability of the molecule arising from hyper conjugative interactions, charge delocalization has been analyzed using NBO analysis. The results show that charge in electron density (ED) in the ?* and ?* anti bonding orbitals and E(2) energies confirms the occurrence of intra molecular charge transfer (ICT) within the molecule. The Himalayan Physics Vol. 3, No. 3 2012 Page : 44-49